2019
DOI: 10.1111/cdep.12349
|View full text |Cite
|
Sign up to set email alerts
|

Studying Executive Function Skills in Young Children in Low‐ and Middle‐Income Countries: Progress and Directions

Abstract: As a culturally universal set of cognitive skills that promote goal-directed behaviors, executive functions (EFs) support milestones of early childhood development, such as learning and forming social relationships. A growing base of evidence shows commonality around the world in EFs' validity, biological basis, and family predictors. But we need more research to understand more fully how to promote the development of EF skills in young children from low-and middle-income countries. In this article, we highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 43 publications
(66 reference statements)
4
44
0
Order By: Relevance
“…In contrast, HCCs were not directly correlated with verbal intelligence or EFs. Although our study cannot address the mechanisms behind this divergent finding, it is feasible that the association between HCC and cognitive skills may differ for crystallized knowledge, deduced from exposure to information and facts, versus fluid cognitive skills, which reflect children's capacity to process and integrate information (Obradović & Willoughby, 2019 (Obradović, 2016). For example, while some previous work has shown that higher physiological reactivity marks greater biological sensitivity to family resources (Ellis, & Boyce, 2011;Essex et al, 2011;Obradović et al, 2010;Obradović, Yousafzai, et al, 2016),…”
Section: Hair Cortisol Concentrations and Cognitive Developmentmentioning
confidence: 78%
See 3 more Smart Citations
“…In contrast, HCCs were not directly correlated with verbal intelligence or EFs. Although our study cannot address the mechanisms behind this divergent finding, it is feasible that the association between HCC and cognitive skills may differ for crystallized knowledge, deduced from exposure to information and facts, versus fluid cognitive skills, which reflect children's capacity to process and integrate information (Obradović & Willoughby, 2019 (Obradović, 2016). For example, while some previous work has shown that higher physiological reactivity marks greater biological sensitivity to family resources (Ellis, & Boyce, 2011;Essex et al, 2011;Obradović et al, 2010;Obradović, Yousafzai, et al, 2016),…”
Section: Hair Cortisol Concentrations and Cognitive Developmentmentioning
confidence: 78%
“…In contrast, HCCs were not directly correlated with verbal intelligence or EFs. Although our study cannot address the mechanisms behind this divergent finding, it is feasible that the association between HCC and cognitive skills may differ for crystallized knowledge, deduced from exposure to information and facts, versus fluid cognitive skills, which reflect children's capacity to process and integrate information (Obradović & Willoughby, 2019). Future research should continue to investigate the associations between stress hormones and different aspects of early cognitive development in children from LMIC settings.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…EF skills can be improved through intervention, and early childhood may be a sensitive period for interventions. Although most of what is known about EF skills is derived from research in high-income countries, EF skills are germane to early learning and school readiness in low- and middle-income countries (LMICs) ( Obradović and Willoughby, 2019 ). There is global interest among educators and policymakers in identifying practical and developmentally appropriate strategies for improving children’s EF skills.…”
Section: Introductionmentioning
confidence: 99%